Association of Diabetes and Insulin Therapy With Risk of Hospitalization for Infection and 28-Day Mortality Risk. (4th December 2016) - Donnelly, John P.; Nair, Sunil; Griffin, Russell; Baddley, John W.; Safford, Monika M.; Wang, Henry E.; Shapiro, Nathan I.
Summary: Among 30 239 community-dwelling adults in the United States, diabetes was associated with increased risk of hospitalization for infection but not 28-day mortality risk. Insulin therapy conferred a greater risk of hospitalization, with no increase in 28-day mortality. Abstract: Background: Epidemiologic and experimental evidence suggests that individuals with diabetes are at increased risk of infection. We sought to examine the association of diabetes and insulin therapy with hospitalization for infection and 28-day mortality. Methods: We performed a prospective cohort study using data from 30 239 community-dwelling participants aged ≥45 years enrolled in the REasons for Geographic and Racial Differences in Stroke (REGARDS) study. We defined diabetes as a fasting glucose level ≥126 mg/L (or ≥200 mg/L for those not fasting), the use of insulin or oral hypoglycemic agents, or self-reported history. We identified infection-related hospitalizations over the years 2003–2012. We fit Cox proportional hazards models to assess the association of diabetes with hazard rates of infection and logistic regression models for 28-day mortality. Results: Among 29 683 patients from the REGARDS study with complete follow-up, 7375 had diabetes. Over a median follow-up period of 6.5 years, we identified 2593 first and 3411 total infection hospitalizations. In adjusted analyses, participants with diabetes had an increased hazard of infection (hazard ratio, 1.50; 95% confidence interval [CI], 1.37–1.64) compared with those without diabetes. Participants with diabetes hospitalized for infection did not have an increased odds of death within 28 days (odds ratio, 0.94; 95% CI, .67–1.32). Participants receiving insulin therapy had greater hazard of infection (hazard ratio, 2.18; 95% CI, 1.90–2.51) but no increased odds of mortality (odd ratio, 1.07; 95% CI, .67–1.71). Conclusions: Diabetes is associated with increased risk of hospitalization for infection. However, we did not find an association with 28-day mortality. Insulin therapy conferred an even greater risk of hospitalization, without increased mortality.